Amylin inhibits bone resorption while the calcitonin receptor controls bone formation in vivo - Dacquin, Romain (The Rockefeller University Press, 2004)
Amylin is a member of the calcitonin family of hormones cosecreted with insulin by pancreatic β cells. Cell culture assays suggest that amylin could affect bone formation and bone resorption, this latter function after its binding to the calcitonin receptor (CALCR). Here we show that Amylin inactivation leads to a low bone mass due to an increase in bone resorption, whereas bone formation is unaffected. In vitro, amylin inhibits fusion of mononucleated osteoclast precursors into multinucleated osteoclasts in an ERK1/2-dependent manner. Although Amylin +/− mice like Amylin-deficient mice display a low bone mass phenotype and increased bone resorption, Calcr +/− mice display a high bone mass due to an increase in bone formation. Moreover, compound heterozygote mice for Calcr and Amylin inactivation displayed bone abnormalities observed in both Calcr +/− and Amylin +/− mice, thereby ruling out that amylin uses CALCR to inhibit osteoclastogenesis in vivo. Thus, amylin is a physiological regulator of bone resorption that acts through an unidentified receptor.